1996
DOI: 10.1152/ajpcell.1996.271.3.c810
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 modulates twitch tension and increases Po of Ca2+ release channel in frog skeletal muscle

Abstract: The effect of H2O2 was examined to elucidate the basis of muscle injury after exercise. Exposure of single fibers to 1.5-6 mM H2O2 led to twitch potentiation followed by a marked decrease. Then, fibers contracted spontaneously. BAY K 8644 augmented twitch potentiation and slowed the decay of twitches. In 5 mM dithiothreitol (DTT), twitch potentiation and spontaneous contraction were not observed on H2O2 addition. Cytoplasmic application of 1.5-3 mM H2O2 to heavy sarcoplasmic reticulum (SR) vesicles incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
5
58
0
2
Order By: Relevance
“…For instance, we found an increase of resting cytosolic Ca 2+ concentration in aged rats (Fraysse et al 2006). Hydrogen peroxide affects the structure and activity of the dihydropyridine and ryanodine receptors and consequently modifies calcium release and muscle contraction (Oba et al 1996;Espinosa et al 2006). The oxidation of SH groups alters L-type channel gating with a reduction of calcium currents in cardiac cells (Lacampagne et al 1995).…”
Section: Introductionmentioning
confidence: 83%
“…For instance, we found an increase of resting cytosolic Ca 2+ concentration in aged rats (Fraysse et al 2006). Hydrogen peroxide affects the structure and activity of the dihydropyridine and ryanodine receptors and consequently modifies calcium release and muscle contraction (Oba et al 1996;Espinosa et al 2006). The oxidation of SH groups alters L-type channel gating with a reduction of calcium currents in cardiac cells (Lacampagne et al 1995).…”
Section: Introductionmentioning
confidence: 83%
“…Oba et al (Oba et al, 1996) reported that incubation of intact single frog fibers in a solution containing H 2 O 2 induced a biphasic effect on muscle force. Initially, muscle force increased, but as the exposure to H 2 O 2 continued, muscle force declined (Oba et al, 1996). Likewise, Andrade et al (Andrade et al, 1998) reported that single mouse fibers responded to H 2 O 2 exposure in a time-dependent manner, showing biphasic changes.…”
Section: Integrating the Redox Homeostasis Responses To Exercise Withmentioning
confidence: 99%
“…Shortly afterwards, several studies verified this hormetic effect of reactive species on muscle force. Oba et al (Oba et al, 1996) reported that incubation of intact single frog fibers in a solution containing H 2 O 2 induced a biphasic effect on muscle force. Initially, muscle force increased, but as the exposure to H 2 O 2 continued, muscle force declined (Oba et al, 1996).…”
mentioning
confidence: 99%
“…Thus the RYR channel, which contains sensitive SH groups, appears a likely target for modification. It has been directly demonstrated that the skeletal muscle RYR channel is sensitive to singlet oxygen (122), hydrogen peroxide (48,99) and hypochlorous acid (128). Recently, Oba et al (99) demonstrated that hydrogen peroxide initially potentiated twitch tension.…”
Section: Failure Of Sr Ca 2ϩ Release and Muscle Fatiguementioning
confidence: 99%